Colloidal Shaping of 8 mol% Yttria‐Stabilized Zirconia Electrolyte Honeycomb Structures by Microwave‐Assisted Thermal Gelation of Methyl Cellulose. Issue 1 (25th October 2012) - Rajeswari, Kotikalapudi; Biswas, Papiya; Suresh, Madireddy Buchi; Hareesh, Unnikrishnan Saraswathy; Johnson, Roy; Das, Dibakar
<x xml:space="preserve">Abstract</x> Eight mol% Yttria‐stabilized zirconia, the most commonly employed electrolyte material for solid oxide fuel cells (SOFC), was shaped into honeycomb structures by thermally induced gelation of aqueous zirconia slurry containing methyl cellulose using microwave irradiation. The green honeycomb samples were subjected to green density and green compressive strength measurements revealing a uniform gelation and hence a relatively higher strength for microwave irradiated samples. The green honeycomb samples were further sintered to crack‐free dense honeycombs (>99% TD) at 1525°C for 1 h. Honeycomb samples were characterized for their physical, cellular, and electrical properties. A relatively high ionic conductivity value of 0.07 S/cm at 800°C and corresponding low activation energy of 0.61 eV in the temperature range 700–800°C provide opportunities to explore the development of novel designs for SOFC application.